A Year in Review. Issue 4 (1st October 2016) - Frederiksen, Linda
Abstract : Column description. The Best of the Literature column is intended to keep librarians, administrators, and staff up to date with the most recent, relevant, and useful literature of the field. Columns may focus on a specific theme or topic or they may be a review of significant or interesting resources published within the past year. Columns generally begin with a brief introduction to the topic or theme of the column and include references and annotations for up to between 7–10 different resources. Readers are invited to suggest themes, topics, or resources to Linda Frederiksen .